Understanding influencing attributes of adolescent snack choices: Evidence from a discrete choice experiment. (September 2021) - Rusmevichientong, Pimbucha; Jaynes, Jessica; Chandler, Laura
Highlights: The study determined influencing snack attributes of adolescent snack choices. A discrete choice experiment quantified the relative importance of snack attributes. Block fractional factorial designs were used to construct discrete choice experiments. The attributes with the highest relative importance were whole grains and price. Students were more attentive to negative nutrients when two attributes interacted. Abstract: The quality of diet is crucial to the health and well-being of America's adolescents. While a critical step in the goal toward healthier eating is facilitated by school nutrition guidelines that address the food environment, additional information on snack preferences can contribute to this goal. The purpose of this study was to determine which snack nutrient and snack characteristic attributes affect adolescent snack choices and quantify their relative importance. The method used in this study was a discrete choice experiment (DCE) designed with a unique approach of block fractional factorial designs. The study participants were middle school students, aged 11 to 13 years old (n=166) from an underrepresented, minority-serving middle school in Orange County, California. A mixed logit model was used to analyze the data from DCEs that examined five snack nutrients and five snack characteristics. The results indicated whole grains had the highest relative importance of snack nutrients followed by salt, protein, calories and sugar. Students were more attentive to negative nutrients when two attributes interacted. Price had the highest relative importance of snack characteristics followed by nutritiousness, social, taste, and convenience. Students were more likely to choose a snack in which their family eats even if the snack was low in nutrient content. Understanding students' preferences can potentially enhance healthy eating practices on school campuses. This provides implications for stakeholders working to implement and comply with federal school nutrition guidelines.